Lokakarya Pendekatan Berpusat pada Siswa: Kunci Perubahan Positif dalam Pendidikan Sekolah Penggerak Angkatan 3 di Kabupaten Bireuen - Muhammad Wali; Noval Fuadi; Muchlisan Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This program has a strong aim to improve the quality of education in Bireuen Regency by focusing on implementing a student-centered approach and the Merdeka Belajar curriculum. Through a series of workshops and intensive collaboration, the program has achieved significant results. The participants, consisting of teachers, supervisors, and principals, have experienced a deeper understanding of the student-centered approach, relevant learning strategies, and the Merdeka Belajar curriculum. The impact can be seen in the development of learning materials that are more suited to students' interests and needs, the creation of an inclusive learning environment, and strict monitoring and evaluation of program implementation. Apart from that, this program also makes a significant contribution in forming more competent educational leaders through the 3rd Generation Driving School Program. The target community for this program involves various stakeholders, including teachers, teaching staff, school principals, supervisors, and other parties. related. With a sharp focus on improving the quality of education, this program aims to have a broad and sustainable positive impact on the world of education in Bireuen Regency. This service activity creates a strong basis for continuous education improvement and strengthens commitment to implementing a student-centered approach and the Merdeka Belajar curriculum as an important foundation in improving the quality of education in Bireuen Regency.